Pengaruh Pelatihan Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Aeon Alam Sutera Tangerang - Anisa Nursa’adah; Risza Putri Elburdah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to examine the effects of training and leadership style on employee performance at Aeon Alam Sutera Tangerang, both partially and simultaneously. This research employs a quantitative method with a population of 211 employees and a sample of 68 respondents. The data used are primary data obtained through questionnaire distribution. Data analysis techniques include research instrument testing (validity and reliability tests), classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), and hypothesis testing using t-tests and an F-test. The results indicate that training (X₁) partially has a positive and significant effect on employee performance (Y), as shown by a t-value of 6.219, which is greater than the t-table value of 1.99714, with a significance level of 0.000 < 0.05. Leadership style (X₂) also partially has a positive and significant effect on employee performance (Y), with a t-value of 4.645, which is greater than the t-table value of 1.99714, and a significance level of 0.000 < 0.05. Furthermore, the F-test results show that the calculated F-value is greater than the F-table value (21.977 > 3.14), with a significance level of 0.000 < 0.05. Therefore, it can be concluded that training and leadership style simultaneously have a positive and significant effect on employee performance at Aeon Alam Sutera Tangerang. The coefficient of determination (R²) value of 0.403 indicates that 40.3% of employee performance is influenced by training and leadership style, while the remaining 59.7% is influenced by other variables not examined in this study